Desarrollo de una herramienta digital para facilidades de producción en el diseño de tratadores térmicos orientado a crudos pesados aplicando la norma API 12L (2020)
Heavy crude oils for the oil industry have always been a challenge, since due to their high content of BSW%, salts and the presence of asphaltenes and paraffins, emulsions are formed that require the fluid to undergo more elaborate treatments, where it is sought that These variables are within the standards established by norms that govern these processes, such as API 12L. In order to achieve a good separation and also a good quality for its commercialization, it is necessary to use specialized equipment such as heat treaters that seek to destabilize all types of mixture seeking great efficiency in the treatment of emulsions as the main problem in production fluids. For this to be possible, a good design and dimensioning of this equipment is necessary and of great importance for good compliance with the separation principles. However, few digital instruments are available that are specialized for this type of fluid that provide fast and efficient responses. For this reason, it is essential to develop a digital tool for production facilities in the design of heat treaters that is oriented to heavy crude oils, applying the API 12L standard.